2022
DOI: 10.3389/fmicb.2022.1032969
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the EnvZ/OmpR two-component system to growth, virulence and stress tolerance of colistin-resistant Aeromonas hydrophila

Abstract: Aeromonas hydrophila is an important zoonotic pathogen responsible for septicemia, diarrhea and gastroenteritis, and has attracted considerable attention. The EnvZ/OmpR two-component system (TCS) mediates environmental stress responses in gram-negative bacteria. We investigated the role of the TCS in A. hydrophila by comparing the characteristics of the parental (23-C-23), EnvZ/OmpR knockout (23-C-23:ΔEnvZ/OmpR), and complemented strains (23-C-23:CΔEnvZ/OmpR). Under non-stress conditions, the 23-C-23:ΔEnvZ/Omp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Our studies also suggest a potential link between EnvZ and bacterial chemotaxis since both mutants bearing SNPs in envZ can also be characterized by an alternated expression of flagellin and other chemotaxis-related proteins and also displayed reduced swarming behavior in our motility assay in vitro . Other studies have already hypothesized that OmpR might negatively regulate the expression of flagella ( 43 45 ) and have also connected NTX to changes in surface adhesion and pilus expression ( 14 , 46 ), without giving an explanation. Our data allow the hypothesis that EnvZ is the key regulatory unit pathing the way for further research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our studies also suggest a potential link between EnvZ and bacterial chemotaxis since both mutants bearing SNPs in envZ can also be characterized by an alternated expression of flagellin and other chemotaxis-related proteins and also displayed reduced swarming behavior in our motility assay in vitro . Other studies have already hypothesized that OmpR might negatively regulate the expression of flagella ( 43 45 ) and have also connected NTX to changes in surface adhesion and pilus expression ( 14 , 46 ), without giving an explanation. Our data allow the hypothesis that EnvZ is the key regulatory unit pathing the way for further research.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the general drop in metabolic activity, downregulation of flagella (FliCN and FlgH) and chemotaxis-related proteins (CheWYZ, Tsr, and Tar) could be a major reason for reduced virulence, as it was previously shown that these can be deemed essential during infection and are required for adhesion to the bladder epithelium ( 47 49 ). Xiao et al already showed that mutations in envZ/ompR will render Aeromonas hydrophila less virulent resulting in higher survival rates of infected mice ( 45 ). This leads us to believe that our findings can also translate into reduced pathogenicity of NTX R E. coli for rodents and humans.…”
Section: Discussionmentioning
confidence: 99%